Digital Twin in Smart Manufacturing: A Systematic Literature Review on Predictive Decision-Making, Industrial Sustainability, and Process Optimization - Fathan Dewadi; Ahmad Royan; Muhammad Nurcholis; Muhammad Pratama (JADI (Jurnal Teknik Industri), 2026)
The rapid advancement of Industry 4.0 has accelerated the adoption of Digital Twin (DT) technology in smart manufacturing systems. DT enables virtual replication of physical assets, supporting real-time monitoring, predictive analytics, simulation, and data-driven decision-making. This systematic literature review investigates the role of Digital Twin technology in predictive decision-making, process optimization, and industrial sustainability within smart manufacturing environments. The review synthesizes recent peer-reviewed studies from Scopus, Web of Science, and IEEE Xplore databases. Findings show that DT enhances operational efficiency through integration with machine learning, cyber-physical systems, and Industrial Internet of Things (IIoT), enabling improved maintenance strategies, energy efficiency, and production optimization. In addition, DT contributes to sustainability by reducing waste generation and supporting circular manufacturing practices. Despite its advantages, implementation challenges remain, including high deployment costs, interoperability issues, cybersecurity risks, and lack of data standardization. Overall, the study concludes that Digital Twin is a key enabling technology for future smart factories, particularly when integrated with artificial intelligence, edge computing, and cloud-based manufacturing systems.